Bioactive profiling and evaluation of anti-proliferative and anti-cancerous properties of Shivagutika, an Indian polyherbal formulation synchronizing in vitro and in silico approaches - V. H., Pushpa; Kuruburu, Mahadevaswamy G.; M. K., Jayanthi; N., Akshaya Simha; Taha Babakr, Abdullatif; Sreenivasan, Rajesh; Ramu, Ramith; Madhunapantula, SubbaRao V. (Frontiers in Chemistry, 2023)
Shivagutika is a polyherbal formulation mentioned in Ayurveda, the oldest system of medicine. The aim of this study was to investigate the anti-breast cancer potential of DCM extract of Shivagutika using MCF-7, MDA-MB-231, and MDA-MB-468. Primarily, various extracts of Shivagutika were prepared and subjected to primary in vitro analysis—total protein, phenolic acid content, and flavonoid content. DCM extract among all the extracts showed the promising results hence, it was subjected to LC-MS/MS analysis to identify the phytochemicals. The same extract was subjected to anti-proliferation assay and anti-cancer assay. It inhibited all the 3 cell lines and increased the activity of Caspase 3, pro-apoptotic protein. Further, to find the potent molecule(s) in silico analysis (molecular docking and molecular dynamics simulation studies) was performed. Sciadopitysin was identified as a potent molecule among all phytochemicals as it interacted with Caspase 3 with a binding energy of −7.2 kcal/mol. MD simulation studies also revealed that Sciadopitysin was stable inside the binding pocket of Caspase 3 by interacting with the amino acids in the catalytic site thereby activating the Caspase 3 levels. By all the above results, Shivagutika could be used as a potent anti-breast cancer agent (specifically DCM extract of Shivagutika) which could decrease the cases of breast cancer in future.